Geochemistry of organic matter in carbonate Devonian sediments of the South Tatar arch - A. Yu. Orlova; R. S. Khisamov; V. G. Bazarevskaya; E. N. Poludetkina; N. P. Fadeeva; T. A. Shardanova (Georesursy, 2024)
The article deals with the lithology and geochemistry of organic matter of Upper Devonian-Lower Carboniferous deposits (Carbonate Devonian) of the eastern part of the South Tatar arch. Rocks of this age have a high generative potential due to increased concentrations of organic matter (OM) and its phytogenic and zoophytogenic composition. They refer to non-traditional sources of hydrocarbons. The generative potential depends on the facial environment and the transformation of OM. The highest potential have carbonate-siliceous and siliceous-carbonate rhythmites domannic horizon.